2011
DOI: 10.1021/jo200354u
|View full text |Cite
|
Sign up to set email alerts
|

C−H Functionalization of 1,4-Naphthoquinone by Oxidative Coupling with Anilines in the Presence of a Catalytic Quantity of Copper(II) Acetate

Abstract: The oxidative addition of anilines (2) with 1,4-naphthoquinone (3) to give N-aryl-2-amino-1,4-naphthoquinones (1) was found to be catalyzed by copper(II) acetate. In the absence of the catalyst, the reactions are slower and give lower yields with the formation of many colateral products. In the presence of 10 mol % hydrated copper(II) acetate, the reactions are generally more efficient in that they are cleaner, higher yielding, and faster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 119 publications
(62 reference statements)
0
58
0
1
Order By: Relevance
“…Based on evidences reported in literature on the use of Lewis acids to promote the oxidative amination reaction of quinones with arylamines, 24 we examined their inuence on the reaction of TMA with quinones 2a and 2d, seeking to facilitate the formation of aminoquinones 4a and 4d with respect to the respective heterocycles 3a and 5a. The assays, performed in the presence of CeCl 3 $7H 2 O and InBr 3 , demonstrate that these Lewis acids do not show signicant changes in the products ratio relative to those obtained in their absence.…”
Section: Resultsmentioning
confidence: 99%
“…Based on evidences reported in literature on the use of Lewis acids to promote the oxidative amination reaction of quinones with arylamines, 24 we examined their inuence on the reaction of TMA with quinones 2a and 2d, seeking to facilitate the formation of aminoquinones 4a and 4d with respect to the respective heterocycles 3a and 5a. The assays, performed in the presence of CeCl 3 $7H 2 O and InBr 3 , demonstrate that these Lewis acids do not show signicant changes in the products ratio relative to those obtained in their absence.…”
Section: Resultsmentioning
confidence: 99%
“…3 In the present study, we have developed upon the method reported by the group of Fagnou (scheme 1). 3d We have investigated the use of other cooxidants (such as Cu(OAc) 2 .H 2 O) and the effect of temperature upon the reaction (Table 1). Initially we reproduced the results of Fagnou and subsequently found that the inclusion of Cu(OAc) 2 .H 2 O had a beneficial effect upon the reaction yield (Table 1, entries 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…2 Additionally, we have now studied the oxidative cyclization (formation of a C-C bond from two C-H bonds) of 2-anilino-and 2-phenyloxy-naphthoquinones.…”
mentioning
confidence: 99%
“…Garden e colaboradores 19 descreveram recentemente a adição oxidativa de anilinas à 1,4-naftoquinona, gerando N-aril-2-amino-1,4-naftoquinonas, catalisada por acetato de cobre (II). Os autores estabeleceram que a ausência do catalisador de ácido de Lewis torna a reação mais lenta e resulta em baixos rendimentos, com a formação de muitos produtos colaterais.…”
Section: Resultsunclassified